Catalytic reduction of p-nitrophenol and Eosin Yellow by lemongrass tea-stabilized copper nanoparticles - Amanda R. Kale; Gillian A. Ferko; Sarah K. St. Angelo (Green Chemistry Letters and Reviews)
Green synthesis of nanoparticles for catalytic applications remains of continued interest, especially for reactions that would occur on an industrial scale or that may be of environmental significance. Here, ultrasmall 2.1-nm copper nanoparticles were synthesized under ambient conditions using a copper sulfate pentahydrate precursor and lemongrass extract as a reducing and capping agent. Their potential to act as catalysts was tested using model reactions: the sodium borohydride reduction reactions of p-nitrophenol and Eosin Yellow. Kinetics measurements were obtained with visible time-course spectroscopy and showed that copper nanoparticles effectively catalyzed both reactions. Temperature dependence followed Arrhenius behavior, indicating the catalyst surface was accessible to reactants. Activation energies of 59.2 and 38.5 kJ/mol were obtained for the reduction reactions of p-nitrophenol and Eosin Yellow, respectively. Large frequency factors for both reactions were found, implying large numbers of catalytic sites and/or facilitation of reaction by capping agents. This copper nanoparticle catalyst prepared via green synthesis demonstrates reproducible reduction behavior for two model reactions and observed rate constants that compare favorably with other copper nanoparticle catalysts, particularly in terms of rate constants normalized for available surface area and including catalysts produced via traditional synthetic methods.